Vellus-to-terminal Hair Follicle Reconversion Occurs in Male Pattern Balding and is Promoted by Minoxidil and Platelet-rich Plasma: In Vivo Evidence from a New Humanized Mouse Model of Androgenetic Alopecia - Amos Gilhar; Aviad Keren; Ralf Paus (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)